Present limits to cosmic bubbles from the COBE-DMR three point correlation function - Corasaniti, Pier Stefano; Amendola, Luca; Occhionero, Franco (Arxiv, 2000)
The existence of large scale voids in several galaxy surveys suggests the occurence of an inflationary first order phase transition. This process generates primordial bubbles that, before evolving into the present voids, leave at decoupling a non-Gaussian imprint on the CMB. I this paper we evaluate an analytical expression of the collapsed three point correlation function from the bubble temperature fluctuations. Comparing the results with COBE-DMR measures, we obtain upper limits on the allowed non-Gaussianity and hence on the bubble parameters.